Adaptation to Skew Distortions of Natural Scenes and Retinal Specificity of Its Aftereffects - Habtegiorgis, Selam W.; Rifai, Katharina; Lappe, Markus; Wahl, Siegfried (Frontiers in Psychology, 2017)
Image skew is one of the prominent distortions that exist in optical elements, such as in spectacle lenses. The present study evaluates adaption to image skew in dynamic natural images. Moreover, the cortical levels involved in skew coding were probed using retinal specificity of skew adaptation aftereffects. Left and right skewed natural image sequences were shown to observers as adapting stimuli. The point of subjective equality (PSE), i.e. the skew amplitude in simple geometrical patterns that is perceived to be unskewed, was used to quantify the aftereffect of each adapting skew direction. The PSE, in a two-alternative forced choice paradigm, shifted towards the adapting skew direction. Moreover, significant adaptation aftereffects were obtained not only at adapted, but also at non-adapted retinal locations during fixation. Skew adaptation information was transferred partially to non-adapted retinal locations. Thus, adaptation to skewed natural scenes induces coordinated plasticity in lower and higher cortical areas of the visual pathway.